Geographical characteristics of Chrsyomya bezziana based on external morphology study - Wardhana, April H.; Muharsini, S; Ready, P.D; Cameron, M.M; Hall, M.J.R (Indonesian Journal of Animal and Veterinary Sciences, 2012)
Correct identification of Chrysomya bezziana is a fundamental step to evaluate the successfulness of the eradication program based on Sterile Insect Techinque (SIT). However, geographical variation of the fly is being controversial among scientists. The aim of the study was to investigate the effect of preservation method on visualisation of characters of external morphology and to analyse geographical variation of C. bezziana populations throughout their distribution regions. A total of 88 flies collected from 7 populations in Indonesia, 2 populations in Africa and each 1 population from Oman, India, Malaysia and Papua New Guinea (PNG) were tested in the study. All larvae were removed from natural myiasis cases. The larvae were reared at laboratory until they became adult flies. The samples were preserved into two methods, wet (80% ethanol) and dried (pin) methods. Ten external characters of head and body were observed.Â  Data were subjected to principal components and hierarchical cluster analyses in UNISTATÃ software. The Euclid distance measure was used for the cluster analysis, and the linking method used was the unweighted pair-group method using arithmetic average (UPGMA), to compute the distance between clusters. Results indicated that dried preservation (pinned samples) provided better external character than ethanol preservation. Based on external morphology of adult stages revealed that C. bezziana occurs as two geographical races, African and Asian races. There was no geographical variation of C. bezziana throughout Indonesian archipelago, except for the population from PNG forming its own cluster. Key Words: Myiasis, Chrysomya bezziana, Morphology, Geographical Variaton